The Responsiveness of Scales to Scientific Research Methodologies in University Theses (American Journal of Arts and Human Science, 2024)
The research aims to define scales and their criteria and measure the extent of research methodologies’ responsiveness to these scales by utilizing a sample comprising 50 university theses and dissertations in the field of information and knowledge technology from 2015 to 2023. A standardized measurement system was constructed to assess the level of research methodologies’ alignment with the established criteria utilized in scientific research. The research adopted a descriptive-analytical approach as the execution method, employing direct examination and reference listing as data collection tools. Data analysis was conducted using Microsoft Excel, and graphical curves were plotted. The results demonstrated the existence of 14 criteria associated with scales that enhance the effectiveness and responsiveness of research methodologies in scientific investigations. The responsiveness levels of research methodologies to the utilized criteria exhibited variation, ranging between 30% and 80%, contingent upon the research domain. The study revealed that the effectiveness ratio of criteria performance in hypothesis achievement within the study domain reached 51%, while the ratio of non-achievement of criteria performance stood at 49%.